2022
DOI: 10.7554/elife.75197
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial human recordings reveal association between neural activity and perceived intensity for the pain of others in the insula

Abstract: Based on neuroimaging data, the insula is considered important for people to empathize with the pain of others. Here we present intracranial electroencephalographic (iEEG) recordings and single-cell recordings from the human insulae while 7 epilepsy patients rated the intensity of a woman's painful experiences seen in short movie clips. Pain had to be deduced from seeing facial expressions or a hand being slapped by a belt. We found activity in the broadband 20-190 Hz range correlated with the trial-by-trial p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 75 publications
(157 reference statements)
3
15
0
Order By: Relevance
“…Within the limitations of fMRI, activity in these regions may thus have played a role in motivating costly helping. This dovetails with findings from previous studies that showed BOLD activity in similar networks of regions scaled with perceived pain in Hollywood-type videos with various intensities of pain (Karjalainen et al, 2017), and for the insula, recent intracranial recordings showing that the power in broadband gamma and the spiking of single neurons in this region scales with the perceived pain intensity for similar stimuli (Soyman et al, 2022). Importantly, this also matches findings using a similar task acquired in a different lab (Ioumpa et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Within the limitations of fMRI, activity in these regions may thus have played a role in motivating costly helping. This dovetails with findings from previous studies that showed BOLD activity in similar networks of regions scaled with perceived pain in Hollywood-type videos with various intensities of pain (Karjalainen et al, 2017), and for the insula, recent intracranial recordings showing that the power in broadband gamma and the spiking of single neurons in this region scales with the perceived pain intensity for similar stimuli (Soyman et al, 2022). Importantly, this also matches findings using a similar task acquired in a different lab (Ioumpa et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous research, insula, ACC activated more strongly as the donation increased (Fig. 4) (Ioumpa et al, 2023;Jackson et al, 2005Jackson et al, , 2006Karjalainen et al, 2017;Lamm et al, 2011;Saarela et al, 2007;Singer et al, 2004;Soyman et al, 2022).…”
Section: Bold-fmri Responses To Vicarious Pain Perceptionsupporting
confidence: 91%
“…The anterior insular cortex (aIC) function is mostly correlated with the emotional processing of pain [ 73 , 74 ], cognitive evaluation of pain [ 75 ], and empathy for pain [ 76 , 77 ]. In a recent study in human subjects, it was shown that the insular cortex codes the perceived intensity of empathic pain [ 78 ]. The pIC and aIC are also temporarily segregated; pain signals arrive in the insula first, in the posterior part, while processing in the anterior insula follows with some delay, indicating a posterior to anterior flow of information [ 46 ].…”
Section: Association Of the Insular Cortex Function And Pain In Human...mentioning
confidence: 99%
“…Moreover, the study of pleasurerelated phenomena has directed attention towards the nucleus accumbens, anterior cingulate cortex, ventral pallidum, and amygdala [55]. The insular cortex, on the other hand, has recently emerged as a key structure for a spectrum of behaviors and affective processes, modulating feeding behavior [56][57][58][59], motivational processes [60], nociceptive processing [61,62], saliency attribution [63,64], anxiety [38,65,66], and social approach behaviors [67][68][69][70]. However, a major challenge in the field lies in objectively quantifying emotions in non-verbal species or animals, where quantification of emotions can be highly subjective.…”
Section: Discussionmentioning
confidence: 99%